Legal Reconstruction of Marriage Dispensations in Indonesia through a Theo-Juridical Approach in the Perspective of the Qur'an - Aisyatul Azizah; Fina Wardani; Siti Khodijah Nurul Aula (Contemporary Quran, 2025)
The Legal Reconstruction of Marriage Dispensation in Indonesia through a Theo-Juridical Approach in the Perspective of the Qur’an aims to re-examine the practice of underage marriage within the context of Islamic law, particularly from the perspective of the Qur’an, and to recommend a form of legal reconstruction within the Indonesian legal system. Child marriage remains a persistent legal and social phenomenon across various regions in Indonesia, despite the revision of the minimum marriageable age through Law Number 16 of 2019. A legal loophole in the form of marriage dispensation, as stated in Article 7 paragraph (2), creates room for practices that contradict the principles of child protection. This study employs a normative-juridical method and thematic (maudhū‘i) interpretation of Qur’anic verses related to marriage, family responsibility, and child protection. The findings indicate that the Qur’an emphasizes not only biological readiness but also intellectual maturity (rushd) as an ideal requirement for marriage. The practice of marriage dispensation is considered inconsistent with maqāṣid al-sharī‘ah, particularly in the aspects of protecting life, intellect, lineage, and the dignity of children. This paper recommends legal reconstruction that includes statutory reform, strengthening of law enforcement structures, and transformation of legal culture in society based on Qur’anic values.